2015
DOI: 10.1186/s13104-015-1621-y
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of demand for condoms to prevent HIV infections among barmaids and guesthouse workers in two districts, Tanzania

Abstract: BackgroundCondoms are scientifically recommended as potential products for preventing infections attributable to human immuno-deficiency viruses (HIV). However, evidence on factors leading to their inadequate use in developing countries is still scanty. This paper reports an exploratory study of factors constraining condoms use in Tanzania from the perspectives of barmaids, guest-house workers and retailers.MethodsData were collected in two districts—Mpwapwa in Dodoma Region and Mbeya Rural in Mbeya Region—bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…This indicates that availability is not the single barrier for accessing and using condoms. Mbubyazi et al reported that short supply of condoms, shyness to be watched while purchasing condoms and prevailing social perception of condoms to have low/no protective efficacy are the reason for unprotected sex among the risk population in Tanzania [42]. Lack of confidence to negotiate condom use and the perception that using a condom is the sign of prostitution are also reasons for unprotected sex in our study.…”
Section: Engaging In Risky Sexual Behavior and Practices Before The Hiv Vaccine Trialmentioning
confidence: 45%
“…This indicates that availability is not the single barrier for accessing and using condoms. Mbubyazi et al reported that short supply of condoms, shyness to be watched while purchasing condoms and prevailing social perception of condoms to have low/no protective efficacy are the reason for unprotected sex among the risk population in Tanzania [42]. Lack of confidence to negotiate condom use and the perception that using a condom is the sign of prostitution are also reasons for unprotected sex in our study.…”
Section: Engaging In Risky Sexual Behavior and Practices Before The Hiv Vaccine Trialmentioning
confidence: 45%
“…Besides the methods listed above, a less complex method is the condom. Scientifically recommended as potential products for preventing infections attributable to human immunodeficiency viruses (HIV), condoms act as a barrier to keep sperm from entering the uterus [13]. Another wearable contraceptive choice is the patch which provides the systemic delivery of steroid hormones by transdermal technology using patches that contain estrogen or estrogen plus a progestin that has been successfully used for contraception [14].…”
Section: Introductionmentioning
confidence: 99%